Chemical Contamination of Water and Sediments in the Pardo River, São Paulo, Brazil. (2016) - Machado, Carolina S.; Alves, Renato I.S.; Fregonesi, Brisa M.; Tonani, Karina A.A.; Martinis, Bruno S.; Sierra, Jordi; Nadal, Martí; Domingo, José L.; Segura-Muñoz, Susana
Abstract: River pollution in urban areas may pose human health risks, due to the exposure to chemicals through direct contact, as well as the intake of contaminated fish, agricultural products and water. Pardo River is an important Brazilian water body which flows through two economically important states (São Paulo and Minas Gerais), and it is currently considered as a future drinking water supply option. In the present study, the concentrations of a number of herbicides (by Gas Chromatography with Nitrogen Phosphorous Detector-GC/NPD) and metals (by Inductively Coupled Plasma Mass Spectrometry-ICP/MS) were determined in samples of water and sediments collected along the Pardo River, São Paulo, Brazil, during wet and dry seasons. The presence of atrazine, ametrine, hexazinone and tebuthiuron was verified in water samples, being maximum levels 0.32, 0.27, 0.21 and 1.02 μg/L, respectively. Cadmium, Cu and Zn maximum levels were above national thresholds according to the CONAMA Resolution No. 357/2005 (3.33, 14.6 and 408 μg/L, respectively). In sediments, the highest concentrations were observed for Al and Mn (29, 414 and 9, 531 mg/kg, respectively). In conclusion, the presence of environmental pollutants in water and sediments from the Pardo River is not insignificant, highlighting the potential risk for the population living nearby and in direct/indirect contact with river water. Metals detected above national thresholds may be coming from urban sewage, mining activities, fertilizers and industrial effluent. As our findings have important public health implications, we suggest a system of monitoring that needs to be implemented and can guide adequate actions to improve the resources quality.